Effects of Child Abuse and Neglect on Oral Hygiene and Nutrition in North Indian School Students: A Cohort Study - Singh, Prerna; Sangwan, Amita; Singh, Saurabh; Gupta, Shalini (Indian Journal of Community Health, 2023)
This study investigated the relationship between dental hygiene and child maltreatment, malnutrition, and overall development. The researchers examined 900 students aged 5-15 years from government schools in Lucknow district, Uttar Pradesh. The study observed nutritional status by assessment of the physiological status of the body based on its height and weight and signs of abuse/neglect. The results showed that 260 abused students had poor dental hygiene, and 236 of them were mild to moderately malnourished. In comparison, 362 non-abused students had dental neglect, and 232 were moderately malnourished. These findings highlight a significant association between dental care neglect, child maltreatment, and malnutrition. It is crucial to address the social stigma surrounding this issue, normalize discussions, and encourage dentists to identify signs of abuse and inform relevant authorities about potential discrepancies.